Longitudinal changes in dry eye symptoms and signs following lifitegrast therapy and relationship to tear osmolarity - Pepose, Jay S (Clin Ophthalmol, 2019)
BACKGROUND: This study measured longitudinal changes in dry eye disease (DED) symptoms and signs following lifitegrast therapy and assessed their relationship to tear osmolarity to test the hypothesis that a decline in tear osmolarity is a reliable leading indicator of subsequent improvement in DED symptoms and signs after initiating lifitegrast treatment. METHODS: This phase IV, prospective, single-arm, open-label, 12-week study enrolled subjects aged ≥18 years with eye dryness score ≥40 (0–100 VAS) and tear osmolarity ≥308 mOsm/L. Subjects were prescribed lifitegrast ophthalmic solution 5%, twice daily in each eye. DED symptoms were assessed via VAS at baseline and 2, 6, and 12 weeks. Signs included tear osmolarity, meibomian gland dysfunction, tear breakup time, and fluorescein corneal staining. In post-hoc analysis, subjects with ≥5 mOsm/L decrease in osmolarity over 12 weeks were Responders. RESULTS: Of 26 subjects in the intent-to-treat population, 23 were female; mean age was 67.4 years. Baseline mean±SD eye dryness was 68.7±16.5 and tear osmolarity was 317.8±8.5 mOsm/L. All seven symptoms (dryness, burning, foreign body sensation, pain, photophobia, itching, blurred vision) declined significantly (P<0.01) from baseline to 6 and 12 weeks. Signs did not change significantly. For 13 Responders, tear osmolarity decreased from baseline to 12 weeks (319.2±8.5 to 300.6±12.3 mOsm/L, P<0.001) and corneal staining trended toward improvement (1.1±0.9 to 0.6±0.7, P=0.136). Among Nonresponders, osmolarity increased from 316.4+8.7 to 329.6+13.9 (P<0.01) and corneal staining showed no change (1.3±0.8 to 1.0±0.7 at 12 weeks, P=0.293). CONCLUSIONS: Lifitegrast reduced DED symptoms among subjects with moderate-to-severe disease (severity defined by VAS for eye dryness). Potential reasons that may underlie the dichotomous effect of drug treatment on tear osmolarity are discussed.